Notes of the Opening of Two Eirde-Houses at Clova, Kildrummy, Aberdeenshire, and of a Cist with an Urn and Flint Implements at New Leslie - Lumsden, Hugh Gordon (Proceedings of the Society of Antiquaries of Scotland, 1877)